Evaluation of a rapid coliform detection kit from clinical mastitis milk using colloidal gold nanoparticle–based immunochromatographic strips - KIKU, Yoshio; NAGASAWA, Yuya; SUGAWARA, Kazue; YABUSAKI, Takahiro; OONO, Kazuyoshi; FUJII, Kento; MAEHANA, Koji; HAYASHI, Tomohito (Journal of Veterinary Medical Science, 2021)
The accurate identification of mastitis‐causing bacteria assists in effective management by both dairy farmers and veterinarians and can be used to implement the selective use of antimicrobials for treatment. The purpose of this study was to evaluate the ability of our developed anti–ribosomal protein-L7/L12 antibody–coated immunochromatographic strip (ICS) test to detect coliforms in milk by comparing the results with the bacteriological culture method. We investigated the performance of the ICS test as compared with the bacteriological culture method using 308 milk samples from clinical bovine mastitis. First, to determine the optimal ICS test cutoff point for detecting coliform mastitis, we developed a receiver-operating characteristic curve. The result showed that the cutoff point was at 0.5 of our index. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value of the ICS test were 81.3%, 84.8%, 69.2%, and 91.54%, respectively. As the clinical signs increased in severity, the F-measure, a weighted harmonic mean of the sensitivity and overall PPV performance, increased. Because it is especially important to treat clinical mastitis appropriately in the early stages of detection, the ICS test, which can be used by both dairy farmers and veterinarians on dairy farms, is considered to be a useful tool for detecting coliform mastitis, which often presents with severe signs.